Formation and migration of α‐dicarbonyl compounds during storage and reheating of a sugary food simulation system. (6th February 2020) - Zhuang, Yuan; Dong, Lu; Wang, Jun‐ping; Wang, Shu‐jun; Wang, Shuo
Abstract: BACKGROUND: The thermal processing of food results in the formation of α ‐dicarbonyl compounds ( α ‐DCs) such as glyoxal (GO), methylglyoxal (MGO), 2, 3‐butanedione (2, 3‐BD), and 3‐deoxyglucosone (3‐DG), which are precursors of potentially harmful advanced glycation end products. Some of the α ‐DCs found in food products might result from chemical deterioration reactions during storage and reheating. A range of sugary food simulation systems were stored at three different temperatures (4, 25, and 37 °C) and reheated using three different processing methods to investigate the formation and migration of α ‐DCs. RESULTS: During 20 days of storage, the concentration of α ‐DCs declined, following which the concentration remained approximately constant. Methylglyoxal was the major α ‐DC affected during storage, its relative content decreasing from 233.71 to 44.12 μg mL −1 in the glucose‐lysine system. The concentration of α ‐DCs decreased with increasing temperature. Microwave reheating increased the formation of α ‐DC compounds. The largest increases in 3‐DG concentrations were observed in the maltose‐lysine systems (24.94 to 35.74 μg mL −1 ). The concentration of α ‐DCs only changed a little in response to reheating at 100 °C, but declined when reheated at 150 °C. CONCLUSION: The concentration of α ‐DCs following storage and reheating depends on the type of sugar, lysine content, temperature, and method of reheating. © 2020 Society of Chemical Industry